2‐oxoglutarate‐dependent dioxygenases drive expansion of steroidal alkaloid structural diversity in the genus Solanum. Issue 4 (28th March 2022) - Sonawane, Prashant D.; Jozwiak, Adam; Barbole, Ranjit; Panda, Sayantan; Abebie, Bekele; Kazachkova, Yana; Gharat, Sachin A.; Ramot, Ofir; Unger, Tamar; Wizler, Guy; Meir, Sagit; Rogachev, Ilana; et al.
Summary: Solanum steroidal glycoalkaloids (SGAs) are renowned defence metabolites exhibiting spectacular structural diversity. Genes and enzymes generating the SGA precursor pathway, SGA scaffold and glycosylated forms have been largely identified. Yet, the majority of downstream metabolic steps creating the vast repertoire of SGAs remain untapped. Here, we discovered that members of the 2‐OXOGLUTARATE‐DEPENDENT DIOXYGENASE (2‐ODD) family play a prominent role in SGA metabolism, carrying out three distinct backbone‐modifying oxidative steps in addition to the three formerly reported pathway reactions. The GLYCOALKALOID METABOLISM34 (GAME34) enzyme catalyses the conversion of core SGAs to habrochaitosides in wild tomato S. habrochaites . Cultivated tomato plants overexpressing GAME34 ectopically accumulate habrochaitosides. These habrochaitoside enriched plants extracts potently inhibit Puccinia spp. spore germination, a significant Solanaceae crops fungal pathogen. Another 2‐ODD enzyme, GAME33, acts as a desaturase (via hydroxylation and E/F ring rearrangement) forming unique, yet unreported SGAs. Conversion of bitter α ‐tomatine to ripe fruit, nonbitter SGAs (e.g. esculeoside A) requires two hydroxylations; while the known GAME31 2‐ODD enzyme catalyses hydroxytomatine formation, we find that GAME40 catalyses the penultimate step in the pathway and generates acetoxy‐hydroxytomatine towards esculeosides accumulation. Our results highlight the significant contribution of 2‐ODD enzymes to the remarkable structural diversity found in plant steroidal specialized metabolism.